Effect of rolling resistance on poling forces and metabolic demands of roller skiing - Millet, G. Y.; Hoffman, M. D.; Candau, R. B.; Buckwalter, J. B.; Clifford, P. S. (Medicine & Science in Sports & Exercise, 1998)
1) The decrease in poling recovery time and increase in cycle rate associated with an increase in roller ski rolling resistance is comparable to the effect previously observed from increasing grade and probably occurs as a means of limiting deceleration. 2) Since changes in rolling resistance do not alter the relationships of RPE and heart rate with VO2, the central cardiovascular adaptations from roller ski training should not be affected by the rolling resistance of the roller skis. 3) Higher resistance roller skis are likely to induce greater upper body aerobic adaptations than lower resistance roller skis.